A gestão dos sujeitos: uma interpelação em forma de cartazes aos usuários do restaurante universitário da UFS (RESUN) - Vieira, Alessandra dos Santos (2020)
According to the assumptions of AD - French discourse analysis, the main purpose of ideology is to constitute “free” individuals as dependent subjects. Bearing in mind that we are subjects challenged by ideology, unconsciously submitted to it, this research sought to analyze the types of speeches that circulate in the external corridors of the UFS - RESUN university restaurant, which challenge users. According to AD, we go through two types of forgetfulness: ideological forgetting - where we have the illusion of being the origin of our saying and forgetting the enunciation - where every saying has already been said, being only taken up in different ways. Thus, throughout this work, we will permeate by categories with which AD works, namely: the interdiscourse, the discursive memories, the production conditions, the discursive formations, the good subject and the bad subject, showing the subject of speech functioning. As for the methodology, the work sought to describe the discursive materiality, that is, the posters, thus appropriating both imagetic and textual discourse. Regarding the constituent elements of the posters, they are plotted on wooden frames, hanging by steel strings scattered on the outer area of the RESUN. The statements of the posters were treated as Cut (R), anchored in the article by Eni Orlandi (1984), which deals with segmentation or cut. Therefore, they are divided by themes, where the sections will be worked: queue, hygiene, discourse of knowledge and management. Since the work uses the notion of “subject of discourse”, this will also be our category of analysis. Thus, we appropriated the theoretical and methodological foundations of the French Discourse Analysis, as proposed by Pêcheux (1993, 2003, 2015), Orlandi (1997, 2008, 2015), Althusser (1998), among other authors. As results obtained, the analysis of the posters allowed us to verify that the meanings produced point to the subject's management, involving users in a discourse, which shows us the subject of the discourse in operation. We also observed that the adoption of good practices suggested in the posters points to the subject of the flow, that is, the one who follows the flow and reproduces the practices in silence.